Common upper extremity gymnastics injuries and gymnastic specific return to play protocols - Elspeth Hart, DScPAS, PA-C, MPAS, ATC, LAT; Andrea S. Bauer, MD; Donald S. Bae, MD (Journal of the Pediatric Orthopaedic Society of North America)
ABSTRACT: Young gymnasts use their upper extremities as weight-bearing joints, imparting high repetitive loads onto the growing upper limb. The purpose of this review is to provide orthopaedic and sports medicine clinicians practical information on the etiology, presentation, and treatment of 5 common upper extremity injuries in the young gymnast: (1) “gymnast wrist” (distal radial physeal injury); (2) grip lock (acute radius and ulna fracture); (3) osteochondritis dissecans of the capitellum; (4) medial tensile injuries of the elbow (medial epicondylar apophysitis, medial epicondyle fractures, and partial or full ulnar collateral ligament tears); and (5) glenohumeral instability (including labrum tears). Specific return to gymnastics protocols are provided to guide providers and athletes through safe return to participation following these injuries. Key Concepts: 1) Gymnastics is a unique sport in which the arms are used as weight-bearing limbs resulting in distinct injuries. 2) Orthopaedic and sports medicine providers should understand these five diagnoses: Gymnast Wrist (distal radial physeal injury and the sequela), Grip Lock (acute radius and ulna fracture), elbow osteochondritis dissecans (OCD), Medial tensile injuries (medial epicondylar apophysitis, medial epicondyle fractures, and partial or full UCL tears), and shoulder instability (including labrum tears) if they will be evaluating gymnasts in their clinic. 3) Pre-determined “return-to-gymnastics” protocols may aid successful progression back to training and competition after upper limb injury.